2012
DOI: 10.1038/ijo.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vitamin D-metabolizing enzymes in human adipose tissue—the effect of obesity and diet-induced weight loss

Abstract: OBJECTIVE: Low vitamin D (VD) levels are common in obesity. We hypothesized that this may be due to metabolism of VD in adipose tissue (AT). Thus, we studied (1) whether the VD-metabolizing enzymes were expressed differently in AT of lean and obese individuals and in visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT), and (2) whether their expression was influenced by weight loss. METHODS: Samples of SAT and VAT were analyzed for expression of the vitamin-D-25-hydroxylases CYP2R1, CYP2J2, CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 56 publications
7
173
0
8
Order By: Relevance
“…However, several confounding factors have not been controlled for in the available data. Excessive weight gain during pregnancy contributes to both the risk of gestational diabetes and low maternal vitamin D levels, as this vitamin is fat soluble and migrates from the blood to fat tissue (47). In addition, higher levels of VDBP in obese patients are associated with a reduced fraction of the bioactive, unbound 15(OH)D (48).…”
Section: Vitamin D Supplementation and Gestational Diabetes Mellitusmentioning
confidence: 99%
“…However, several confounding factors have not been controlled for in the available data. Excessive weight gain during pregnancy contributes to both the risk of gestational diabetes and low maternal vitamin D levels, as this vitamin is fat soluble and migrates from the blood to fat tissue (47). In addition, higher levels of VDBP in obese patients are associated with a reduced fraction of the bioactive, unbound 15(OH)D (48).…”
Section: Vitamin D Supplementation and Gestational Diabetes Mellitusmentioning
confidence: 99%
“…The production of 1,25(OH) 2 D from 25(OH)D was then confirmed by Ching et al (44) and Nimitphong et al (45) . CYP27B1 expression has also been detected in murine adipocytes (43) and in human adipose tissue biopsies (38) . (40) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 96%
“…The presence of VDR in adipose tissue was first reported in the early 1990s (52) and has since been widely confirmed. Interestingly, it was recently found that VDR expression is increased in obese compared with lean subjects (38,53) , but the physiological relevance of this up-regulation has not yet been elucidated.…”
Section: Vitamin D Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several weight loss/diet interventions have measured vitamin D before and after weight loss (see Table 4). Recently, Wamberg et al 32 observed a 27 % increase in 25OHD levels after 11 % weight loss and found the relative change in 25OHD levels correlated with relative weight loss. Another study found a similar increase in 25OHD levels (31 %) following 16 weeks of dietary support (14 % weight and 24 % fat mass loss) and there was a strong correlation between change in 25OHD levels and weight loss and a smaller but still significant correlation with fat mass changes.…”
Section: Do 25-hydroxyvitamin D Levels Change With Weight Loss?mentioning
confidence: 99%